2001
DOI: 10.1038/modpathol.3880367
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of P-Cadherin in Infiltrating Ductal Breast Carcinoma

Abstract: We have immunohistochemically investigated P-cadherin (P-CD) expression in a series of 210 infiltrating ductal carcinomas (IDC) in an attempt to assess the biological and prognostic relevance of P-CD in patients harboring IDCs. Although only 74/210 (35%) of IDCs expressed P-CD in >5% of tumor cells (P-CD-positive carcinomas), categorical analyses revealed that P-CD-positive IDCs were larger (26 ؎ 21 cm versus 22 ؎ 11 cm, P ‫؍‬ .0568), of higher histological grade (P ‫؍‬ .0001), and had more lymph node metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
2
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 18 publications
8
103
2
4
Order By: Relevance
“…Examples of negative and positive tumours are shown in Figure 1k and l, respectively. In poorly di erentiated IDCs, a reduction in E-cadherin expression is frequently associated with anomalous P-cadherin expression, suggesting the presence of common regulatory mechanisms (Palacios et al, 1995;Gamallo et al, 2001). However, in this study no correlation between P-cadherin and Snail expression was observed (P=0.29).…”
contrasting
confidence: 54%
“…Examples of negative and positive tumours are shown in Figure 1k and l, respectively. In poorly di erentiated IDCs, a reduction in E-cadherin expression is frequently associated with anomalous P-cadherin expression, suggesting the presence of common regulatory mechanisms (Palacios et al, 1995;Gamallo et al, 2001). However, in this study no correlation between P-cadherin and Snail expression was observed (P=0.29).…”
contrasting
confidence: 54%
“…Previous studies have shown that P-cadherin expression in breast carcinomas is able to identify a subgroup of lesions with a more aggressive behaviour and poor patient survival (Peralta Soler et al, 1999;Gamallo et al, 2001;Paredes et al, 2002Paredes et al, , 2004Paredes et al, , 2005Paredes et al, , 2008. Similar associations between P-cadherin expression and poor prognosis are described in other cancer models, namely endometrial, cervical, gastric and pancreatic carcinomas (Stefansson et al, 2004;Longatto Filho et al, 2005;Taniuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, these tumours overexpress P-cadherin, maintaining the normal E-cadherin expression (Paredes et al, , 2008. In clinical terms, these P-cadherin-overexpressing tumours present high histological grade, with decreased cell polarity, aggressive behaviour and worse patient survival (Peralta Soler et al, 1999;Gamallo et al, 2001;Paredes et al, 2002Paredes et al, , 2005. On the basis of these observations, we aimed to understand how P-cadherin, in an E-cadherin wild-type background, could influence the behaviour of these tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked the expression of basal markers to increased proliferation, absence of ER, a characteristic growth pattern, and poor prognosis. 79,80,87,88 Recently, Sorlie et al, 89 reanalyzing cDNA microarray data from van't Veer et al, 90 which included 18 BRCA1 and two BRCA2 carcinomas, observed that 80% of BRCA1 carcinomas had a basal-type gene expression profile. Subsequently, Foulkes et al 91 and Palacios et al 92 found a high prevalence of tumors with a basal phenotype among BRCA1-mutation carriers.…”
Section: Brca1 Carcinomas and The Basal Cell Phenotypementioning
confidence: 99%